Peranan Teknologi Augmented Reality Sebagai Media Pembelajaran di Masa Pandemi Covid-19 - Haida Dafitri; Arief Budiman; Fakhrana Nadhila (Program Studi Sistem Informasi, 2020)
Since the COVID-19 pandemic, every learning has to be done online, even though vocational institutions require more practice. So far, students are only given video tutorials on practical learning methods that are felt to be less effective, because students cannot directly touch the items, so it is still not optimal. This condition also makes the motivation and interest and curiosity of students in learning decrease. These situations and conditions require teachers to think creatively and innovatively in designing and implementing learning to take place effectively. One way that can be done by teachers by utilizing the latest technologies that are increasingly sophisticated as learning media. Augmented Reality technology is an alternative solution that can be used as a learning medium. Augmented Reality is an attempt to combine the real world and the virtual world created through a computer so that the boundary between the two becomes very thin. The results of this study are to produce an application that runs on the Android platform by implementing Augmented Reality as a support in learning media activities in the Audio Video Technical Vocational High School. Keywords: Augmented Reality, Android, COVID-19, Learning Media